An optimized toolkit for high molecular weight DNA extraction and ultra-long-read nanopore sequencing using glass beads and hexamminecobalt(III) chloride - Cahyani, Inswasti; Tyson, John; Holmes, Nadine; Quick, Joshua; Moore, Chris; Loman, Nicholas James; Loose, Matt (Genome Research, 2025)
Since the advent of long- read sequencing, achieving longer read lengths has been a key goal for many users. Ultra-long read sets (N50 > 100 kb) produced from Oxford Nanopore sequencers have improved genome assemblies in recent years. However, despite progress in extraction protocols and library preparation methods, ultra-long sequencing remains challenging for many sample types. Here we compare various methods and introduce the FindingNemo protocol that: (1) optimizes ultra-high molecular weight (UHMW) DNA extraction and library clean-up by using glass beads and Hexamminecobalt(III) chloride (CoHex), (2) can deliver high ultra-long sequencing yield of >20 Gb of reads from a single MinION flow cell or >100 Gb from PromethION devices (R9.4 to R10.4 pore variants), and (3) is scalable to using fewer input cells or lower DNA amounts, with extraction to sequencing possible in a single working day. By comparison, we demonstrate that this protocol surpasses previous methods by enabling precise determination of input DNA quantity and quality through cell counting, sample dilution, and homogenization techniques.
10.1101/gr.279943.124